Global research trends of home pharmaceutical care: a bibliometric analysis via CiteSpace - Wu, Qingfang; Feng, Xiaorong; Shen, Chao; Liu, Ying; Yang, Shiwen; Su, Na (Frontiers in Medicine, 2025)
BackgroundThis study aimed to systematically review the research on home pharmaceutical care and to identify emerging trends and research hotspots using bibliometric methods.MethodsPublications related to home pharmaceutical care, published from inception to 6 February 2025, were extracted from the Web of Science Core Collection (WoSCC). The bibliometric tool CiteSpace was employed to analyze various metrics, including the number of publications, contributing countries, institutions, authors, keywords, cited references, and research trends in the field of home pharmaceutical care.ResultsA total of 812 relevant articles were retrieved from the WoSCC. The most prolific contributors were Hughes CM, Nishtala, PS, and Lapane KL. The United States emerged as the leading country in the field, with Queen’s University Belfast identified as the most productive institution. The keyword with the highest frequency was “pharmaceutical care.” The research hotspots in this field were centered around “polypharmacy,” “medication reconciliation,” and “drug-related problems.”ConclusionThis study utilized CiteSpace to analyze research trends and hotspots in the field of home pharmaceutical care. The findings suggest that “polypharmacy” and “care homes” are likely to become focal points of future research. Additionally, the development of research in developing countries lags behind that in developed countries. Therefore, it is crucial for developing countries to learn from the advances made by developed nations in this field, and to foster greater international collaboration and research efforts.